REFRAMING INVESTMENT DETERMINANTS IN EMERGING ECONOMIES: A CONCEPTUAL MODEL BASED ON THE IS SUCCESS FRAMEWORK - Muji Muji; Agustinus Purna Irawan; Cokki Cokki; Haris Maupa; Aang Subiyakto (International Journal of Application on Economics and Business, 2026)
Investment is a core driver of economic development through the generation of growth, job opportunities, and access to technology. This phenomenon may not be true in many developing countries, including Indonesia; in reality, actual investment realization often falls short of policy targets, thus creating a gap between potential and realized outcomes. Whereas most macro-analyses of the investment climate have concentrated on the external determinants such as regulations, macro-analyses view the investment climate in terms of external factors such as infrastructure and tax incentives, and how these influence overall attractiveness for foreign investment; one less explored area is in understanding the psychological processes by which these external policies get translated into investors' decisions. This paper aims to construct a theoretical framework that delineates the factors determining investment in Indonesia using theory-building techniques. The Information Systems (IS) Success Model by DeLone and McLean was adapted and reconceptualized in the investment context through a dual mediation mechanism: investor satisfaction and investor trust. The proposed model established that four external factors—law and regulation, land, labor, and taxation were not directly related to investment decisions but instead acted through investor perceptions. Satisfaction reflected short-term evaluations of current experiences, whereas trust represented long-term confidence in the system's stability and reliability. The fundamental theoretical contribution of this study is an integrative framework clarifying the pathway from policy inputs to psychological responses to investments. This conceptual model is intended to be validated through future empirical studies, utilizing survey-based research and Structural Equation Modeling (SEM).